Association of Brain CD163 Expression and Brain Injury/Hydrocephalus Development in a Rat Model of Subarachnoid Hemorrhage - Jing, Chaohui; Zhang, Haining; Shishido, Hajime; Keep, Richard F.; Hua, Ya (Frontiers in Neuroscience, 2018)
Hemoglobin contributes to brain cell damage and death following subarachnoid hemorrhage (SAH). While CD163, a hemoglobin scavenger receptor, can mediate the clearance of extracellular hemoglobin it has not been well studied in SAH. In the current study, a filament perforation SAH model was performed in male rats. T2-weighted and T2*-weighted scans were carried out using a 7.0-Tesla MR scanner 24 hours after perforation. T2 lesions and hydrocephalus were determined on T2-weighted images. A grading system based on MRI was used to assess SAH severity. The effects of SAH on CD163 were determined by immunohistochemistry staining and Western blots. SAH led to a marked increase in CD163 levels in cortex, white matter and periventricular regions from day 1 to day 7. CD163 stained cells were co-localized with neurons, microglia/macrophages, oligodendrocytes and cleaved caspase-3-positive cells, but not astrocytes. Furthermore, CD163 protein levels were increased in rats with higher SAH grades, the presence of T2 lesions on MRI, or hydrocephalus. In conclusion, CD163 expression is markedly upregulated after SAH. It is associated with more severe hemorrhage, MRI T2 lesion and hydrocephalus development.